Implementasi Metode Pembelajaran Interaktif Guna Meningkatkan Motivasi Belajar Siswa Panti Asuhan Al-Firdaus Karang Joang Balikpapan Utara - Annisa Rahmita Soemarsono; Lusi Ernawati; Farida Nur Hayati (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The impact of the Covid-19 pandemic has affected almost all areas of life, including in the field of education. Changes in the learning system from offline (offline) to online cause several obstacles that must be faced, both by teachers and students. Students must be prepared to face all learning conditions in the future, especially when entering the new normal period. Students who are getting used to the online learning environment must then face the offline learning environment again in the new normal era. Education in the pandemic and post-pandemic eras greatly influences students' interest in learning. Changes in the learning environment that trigger a decrease in student interest in learning affect student learning outcomes. Students at the Al-Firdaus Orphanage KM 9, Karang Joang, North Balikpapan experienced a decrease in student motivation and interest in learning. In order to increase the motivation and interest in learning of the students at the orphanage, community service activities were carried out implementing interactive learning methods. The implementation of interactive learning methods is carried out by dividing study groups. In delivering the material, the presenter also utilizes learning media. At the end of the learning session, several participants were accompanied by a speaker presenting the learning outcomes that had been received. Based on the results of the questionnaire, it can be seen that the activity participants were satisfied with the implementation of these service activities. Some suggestions were also given by activity participants for further activities. These suggestions include adding games/games in between learning activities, increasing the duration of learning activities, and adding subjects other than Mathematics.